Pelatihan Literasi Keuangan bagi UMKM di Distrik Heram: Pengabdian - Rizka Aisyah Nurjannah; Putri Ratnasari; Yulianti Karoma (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Financial literacy is a crucial competency for MSMEs to maintain business sustainability. In Heram District, most MSMEs lack understanding of transaction recording, separating personal and business finances, and simple cash flow reports. This community service activity aims to improve financial literacy through practical training based on local needs. The methods used include interactive lectures, financial recording simulations, and individual mentoring. Evaluation was conducted through pre-post tests, observations, and interviews. Results showed a 41.4% increase in participants' understanding scores, and the majority were able to prepare simple financial reports. The participatory approach and hands-on practice effectively built participants' skills, especially those with limited educational backgrounds. The training also changed participants' attitudes toward the importance of financial recording and cash management and encouraged the formation of a potentially sustainable learning community. This program contributes to financial inclusion and local economic empowerment.